Modeling Ion Channels Using Poisson–Nernst–Planck Theory as an Integrated Approach To Introducing Nanotechnology Concepts: The PNP Cyclic Peptide Ion Channel Model - Radak, Brian; Hwang, Hyonseok; Schatz, George C (Journal of chemical education, 2008)
One of the most fundamental challenges in biochemistry and biophysics is describing the function of ion channels, proteins that control ion transport across cell membranes. One approach to this problem is the application of Poisson–Nernst–Planck (PNP) theory. In practice, applying PNP theory involves creating a computational model of the ion channel and generating a numerical solution of differential equations that describes ion transport and electrostatic interactions. The PNP Cyclic Peptide Ion Channel Model is a simulation tool designed to offer an integrated approach to this important problem in bionanotechnology by demonstrating and explaining the application of PNP theory in a way that is accessible to students at an upper undergraduate level. The program interface was made using the free Rapid Application Infrastructure (Rappture) software made available by the Network for Computational Nanotechnology (NCN). Rappture is designed specifically for Web-based applications. Here we introduce a free version of the PNP Cyclic Peptide Ion Channel Model for use in the simulation of ion transport properties for a model ion channel structure that has been the subject of recent experiments.